Impact of pre-existing history of heart failure on patient profile, therapeutic management and prognosis in cardiogenic shock: Insights from the FRENSHOCK registry. (3rd May 2023) - Schurtz, G; Delmas, C; Fenouillet, M; Roubille, F; Puymirat, E; Leurent, G; Ternacle, J; Harbaoui, B; Combaret, N; Lattuca, B; Bruel, C; Bourenne, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Emergency and Acute Cardiovascular Care Working Group from the French Society of Cardiology Aims: There is a large heterogeneity in patients presenting with cardiogenic shock (CS). To better apprehend this heterogeneity is crucial to adapt treatment and improve prognosis in these severe patients. Of note the presence (or absence) of a pre-existing history of chronic heart failure (CHF) at time of CS onset may be entire part of this heterogeneity and data focusing on this aspect are lacking. Methods: We aimed to compare CS patients with new-onset HF to those with worsening CHF in the multicenter FRENSHOCK registry. Altogether, 772 CS patients were prospectively included: 433 with a previous history of CHF and 339 without. Worsening CHF patients were older (68 +/- 13.4 vs. 62.7 +/- 16.2, p<0.001) and had a greater burden of extra-cardiac co-morbidities. At admission, acute myocardial infarction was predominantly observed in the new-onset HF group (49.9% vs. 25.6%, p<0.001). When focusing on hemodynamic parameters, worsening CHF patients showed more congestion and higher ventricular filling pressures. Worsening CHF patients experienced higher in-hospital all-cause mortality (31.3% vs. 24.2%, p=0.029). Conclusions: Our results emphasize the great heterogeneity of the patients presenting with CS. Worsening CHF patients had higher risk profile and this translated in a 30% increase in in-hospital all-cause mortality. The heterogeneity of this population prompts us to better determine the phenotype of CS patients to adapt their management. Baseline characteristics All-cause in-hospital mortality